Якість життя особистості в період виходу на пенсію - Магдисюк, Людмила Іванівна; Mahdysiuk, Liudmyla I. (Рівненський державний гуманітарний університет, 2016)
У статті представлено проблему вивчення якості життя особистості в період виходу на пенсію. Окреслено специфіку феномена якості життя, психологічні та фізіологічні ознаки осіб пізньої зрілості. Зазначено, що якість життя особистості в період виходу на пенсію залежить від стану здоров’я, фінансової сторони, відпочинку, матеріальних, культурних та духовних потреб, стресів та тривог, рівня освіти, сформованості духовності та світогляду.

The paper presents the problem study of the quality of human life at the time of retirement. The study defines specificity of human life quality phenomenon, psychological quality and physiological signs of late middle aged people. The results of theoretical evaluation of foreign literature on the psychology viewing a problem of entering retirement, give an option of defining three major lines of conceptualizing this issue: retirement age as a decision; retirement age as an adaptation; and retirement age as a stage of professional dynamics. Temporal approach is one of the widely used approaches for studying the period of retirement as a process. It is noted that the life of a person at the time of entering retirement depends on the state of health, financial aspect, relaxation, material, cultural and spiritual requirements, stress and anxiety, level of education, spiritual formedness and mindset. The study has specified the tasks of late middle aged people which determine major events of this period, as well as issues of the development of man. The major ways of late middle aged people development have been determined. The research has proved that conditioned upon the lack of physical activity and no trainings, psychomotor abilities (movement skills) change for the worse. Changes in the anatomy and functions of the internal parts of the body and the body system, and sensory functions are in process (decrement in visual acuity, the sensorial area structure changes; decrease in hearing: first, the troubles in hearing high frequencies occur, then midrange frequencies, and, finally, low frequencies; gustation, olfactive sensitivity and the sensitivity to pain lower). A number of inner and outer indicators of aging are listed: skin dryness and wrinkles; greying and hair loss; muscle loss and adynamia; blood vessel laxity; chronic illness progression; psychophysiological insomnia; defense system decline; temperature imbalance; bone absorption; osteochondrosis; inclined posture.
Human life quality at the time of retirement
Keywords: вихід на пенсію; особистість; здоров’я; благополуччя; якість життя; пізня зрілість; пенсія; задоволеність життям; entering retirement; personality; health; life quality; late middle age; retirement; life satisfaction.; well-being